2014
DOI: 10.2133/dmpk.dmpk-13-rg-059
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Human UDP-glucuronosyltransferases Responsible for the Glucuronidation of Fraxetin

Abstract: Fraxetin, a major constituent of the traditional medicine plant Fraxinus rhynchophylla Hance (Oleaceae), has been found to possess multiple bioactivities. However, the metabolic pathway(s) of fraxetin in human tissues has not been reported yet. This study aimed to characterize the glucuronidation pathway(s) of fraxetin in human tissues. Fraxetin could be metabolized to two glucuronides in human liver microsomes (HLMs). These two glucuronides were biosynthesized and characterized as 7-O-glucuronide (7-O-G) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…In the sugar moiety, the G1 protons and carbons exhibited characteristic chemical shifts near 5 and 100 ppm, whereas the G6 carbon (‐COOH) showed chemical shifts of approximately 170 ppm. In addition, the β ‐configuration of the glucuronic acid moiety was confirmed by the coupling constant of the anomeric proton (δ5.01, J = 7.0 Hz), which agreed well with previous reports regarding the O‐glucuronides [19]. All these evidence clearly demonstrated that the glucuronidation site was located at the C‐4′ phenolic group of AR and the glucuronide was identified as AR‐4′‐O‐glucuronide (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…In the sugar moiety, the G1 protons and carbons exhibited characteristic chemical shifts near 5 and 100 ppm, whereas the G6 carbon (‐COOH) showed chemical shifts of approximately 170 ppm. In addition, the β ‐configuration of the glucuronic acid moiety was confirmed by the coupling constant of the anomeric proton (δ5.01, J = 7.0 Hz), which agreed well with previous reports regarding the O‐glucuronides [19]. All these evidence clearly demonstrated that the glucuronidation site was located at the C‐4′ phenolic group of AR and the glucuronide was identified as AR‐4′‐O‐glucuronide (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…These findings suggest that the C-7 phenol group should receive more attention in further structure modifications aimed toward increasing the metabolic stability of 6,7-DHCs. To date, UGT1A6 and 1A9 have been identified as the major enzymes catalyzing C-7 glucuronidation of coumarins, including 4-MU, daphnetin, and fraxetin (Tukey and Strassburg, 2000;Liang et al, 2010;Xia et al, 2014). In our study, UGT1A6 and UGT1A9 were also effective in 7-O-glucuronidation of 6,7-DHCs.…”
Section: Discussionsupporting
confidence: 51%
“…For example, 4-methylumbelliferone (Tukey and Strassburg, 2000), daphnetin , and fraxetin (Xia et al, 2014) are quickly metabolized by various human UDP-glucuronosyltransferases (UGTs) with high hepatic clearance. Although most UGT1A isoforms are involved, previous studies demonstrated that UGT1A6 and UGT1A9 were the major enzymes catalyzing 7-O-glucuronidation and 8-Oglucuronidation of 7,8-DHCs Xia et al, 2014). However, the glucuronidation positions of 6,7-DHCs and the involved human enzymes have yet to be characterized, which would be necessary before making structural modifications to improve their metabolic stability.…”
Section: Introductionmentioning
confidence: 99%
“…UGTs are a superfamily of isoforms known to have distinct, but overlapping, substrate selectivities, yet the underlying mechanism governing the observed selectivity is not completely understood (Radominska-Pandya, et al, 1999;Sorich, et al, 2004;Miners, et al, 2010;Wu et al, 2012). Generally, UGT1A9 has been shown to prefer sterically hindered nucleophiles bound to an aromatic ring (e.g., propofol; Lee et al, 2003;Sorich et al, 2004;Xia et al, 2014), though this does not fit the chemical structure of EPA. Additionally, UGT1A9 is known to glucuronidate N-hydroxylated arylamines and by extension was found to be the major isoform responsible for O-glucuronidation of benzamidoxime (Fröhlich et al, 2005).…”
Section: Discussionmentioning
confidence: 99%